Effect of the Carbon Support on the Catalytic Activity of Ruthenium‐Magnetite Catalysts for p‐Chloronitrobenzene Hydrogenation. Issue 18 (27th July 2015) - Bertolucci, Elisa; Bacsa, Revathi; Benyounes, Anas; Raspolli‐Galletti, Anna M.; Axet, M. Rosa; Serp, Philippe
Abstract Few‐layer graphene, carbon nanotubes, and N‐doped carbon nanotubes have been used to support Ru and/or Fe3O4 nanoparticles. The materials were prepared by a new single‐step sustainable method that involves: 1) a simple procedure, 2) the use of propanol as a solvent, 3) short reaction times, 4) an efficient and energy‐saving heat source, and 5) the absence of any high‐boiling‐point stabilizing agent or organic surfactant. The supported nanoparticles were characterized by TEM, XRD, inductively coupled plasma optical emission spectroscopy, and SQUID magnetometer analyses and employed in the selective hydrogenation of p‐chloronitrobenzene to p‐chloroaniline with very promising results. The hydrogenation runs evidence the marked influence of the diverse carbon nanostructures on the reaction rate, and highlights the promising activity of nanocatalysts supported on few‐layer graphene.